215 Increased Atherosclerotic Plaque Macrophage Content following Streptococcus Pneumoniae Pneumonia. (6th June 2015) - Bazaz, Rohit; Francis, Sheila; Dockrell, David
Abstract : Background: Clinical studies consistently find an increase in the risk of acute coronary syndrome (ACS) within 1–2 weeks after a respiratory infection. It has yet to be established whether a causal relationship exists. Post mortem studies have revealed that the majority of ACS events occur as a result of atherosclerotic plaque disruption. We hypothesise that the systemic inflammatory response to pneumonia leads to acute localised inflammatory changes within established atherosclerotic plaques, favouring plaque instability, thereby resulting in ACS. Our objective was to investigate the effect of resolving pneumonia on atherosclerotic plaque composition. Materials and methods: 11–13 week old male ApoE -/- mice, a well-established model of atherosclerosis, were fed an atherogenic diet for 7–8 weeks before intranasal infection with 5 × 10 5 cfu type 4 Streptococcus pneumoniae or mock infection. All mice received 3 doses of 100 mg/kg subcutaneous amoxicillin, 12 hly, the first dose given at 24 h post infection. Mice were sacrificed 2 weeks post infection and the heart and brachiocephalic artery excised. Formalin fixed, paraffin embedded aortic sinus and brachiocephalic artery atherosclerotic plaque sections were analysed by histological and immunohistochemical staining. Results: This model of atherosclerotic plaque development following pneumonia resulted in high rates of bacteraemia at 24 h post infection and high survival rates at 5 days post infection (92% and 83% respectively). Streptococcus pneumoniae infection was associated with significantly increased aortic sinus atherosclerotic plaque macrophage content (18.1 vs. 8.0%; p < 0.05) (Figure 1 ). No significant differences in aortic sinus plaque burden, smooth muscle or collagen content were found following infection. Relatively few mice developed significant atherosclerosis at the level of the brachiocephalic artery and no significant differences were found between the two groups in plaques at this site, including buried cap formation. Discussion: In this murine model, pneumococcal pneumonia resulted in increased atherosclerotic plaque macrophage content, a marker of plaque instability. Pneumonia may therefore lead to an increased propensity for atherosclerotic plaques to rupture, although further work is required to assess the polarisation of macrophages in atherosclerotic plaques post pneumonia.